Impact of the COVID-19 Pandemic Regulations on the Health Status and Medical Care of Children with Trisomy 21 - Niemann, Annika; Boudriot, Anett; Brett, Birgit; Fritzsch, Christiane; Götz, Dorit; Haase, Roland; Höhne, Sibylle; Jorch, Gerhard; Köhn, Andrea; Lux, Anke; Zenker, Martin; Rissmann, Anke (Klinische Pädiatrie, 2022)
Background While children are considered at low risk for COVID-19, little is known about the impact of SARS-CoV-2 on paediatric risk patients like children with Trisomy 21 (T21). As these children often need regular therapy and various medical appointments, this study aimed to investigate the possible impact of the COVID-19 pandemic on children with T21.Patients and Methods Parents of children with T21 in the age of 0–12 years in Saxony-Anhalt were interviewed via phone in June 2021 regarding the health status and medical care of their children during the past 15 months of pandemic.Results 37 children with mean age of 6.1 years (min 0; max 12) were included in the study. The majority did not have any additional congenital anomalies. Surveyed parents hardly reported adverse changes of health status during the pandemic, but rather improvements, such as decreased number of respiratory infections and more time spend with their children. Outpatient appointments and therapy were cancelled or postponed at the onset of the pandemic, but parents reported low impact on their child’s health and development. The main concern seemed to be lack of childcare during school and day-care closures and uncertainty concerning possible health impacts of an infection on their children.Conclusion There was low impact of the COVID-19 pandemic on health and medical care of children with T21 in our study population. Further research is needed to help weigh the child’s individual risk of infection against the need for medical treatment and therapy when dealing with paediatric risk patients.
Keywords: Trisomy 21; COVID-19; pandemic; lockdown; pediatric care; health status